Periodontal Status of Patients Undergoing Hemodialysis Therapy in a Tertiary Level Hospital of Nepal - Rana, Sweta Rajya Laxmi; Sharma, Arun (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Periodontitis is a chronic inflammation of the supporting structures of the teeth. It has been shown to be associated with systemic diseases including cardiovascular and respiratory diseases, diabetes mellitus and preterm birth. Conflicting reports on the relationship of chronic renal failure patients and periodontal diseases are present in the literature. No previous study has been reported in renal patients in Nepalese population. Hence this study was done to assess the oral hygiene and periodontal conditions in hemodialysis patients in a Tertiary level hospital in Nepal. Methods: Descriptive observational study in which hemodialysis cases were assessed for periodontal parameters including Oral Hygiene- Simplified Index (OHI-S), Plaque Index (PI), Gingival Index (GI), Probing pocket depth (PPD) and clinical attachment level (CAL). Results: A total of 30 patients (20 male, 10 female; mean age 51.06±14.37 years) were assessed. Mean OHI-S, PI, GI, PPD and CAL were 4.02±0.89, 1.93±0.27, 1.57±0.28, 2.09±0.19 and 2.18±0.42, respectively. The distribution of periodontitis was 10% severe, 46.66% moderate and 43.33% mild periodontitis. Conclusions: Hemodialysis patients showed poor oral hygiene and moderate and periodontitis. Hence periodic assessment and periodontal treatment may prevent further complications in these patients.